A neoclassical-realist analysis of Japan’s stance on cross-strait relations [version 2; peer review: 2 approved] - Karol Zakowski (Stosunki Międzynarodowe, 2023)
Since 1972, Tokyo has maintained official diplomatic relations with Beijing, while stressing the importance of peace and stability across the Taiwan Strait. Based on governmental documents and decision-makers’ political declarations, this article examines Japan’s approach towards cross-strait relations since the 1990s. It applies the perspective of neoclassical realism by analyzing both the international determinants (independent variables) and the domestic factors (intervening variables) behind Tokyo’s approach to ‘One China’ policy. The article tries to answer the question why different Japanese governments reacted in various ways to cross-strait frictions and rapprochement. It is argued that the level of Tokyo’s involvement in the Taiwan problem was dependent both on international and domestic factors. Growing concerns about China’s military buildup, coupled with a gradual demise of pro-Beijing faction in the Liberal Democratic Party, pushed Japan towards containing the People’s Republic of China (PRC) while ameliorating relations with Taipei. As Sino-Japanese relations deteriorated, Tokyo became less inclined to lecture Taiwan against provoking Beijing and more willing to support Taipei’s international initiatives. At the same time, Japan started perceiving cross-strait rapprochement not only as a factor stabilizing the regional security system, but also as a potential threat to national security.